(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
تهدف هذه الدراسة إلى تحديد الآثار الاقتصادية للاستثمار الحكومي في قطاع الإسكان في سورية. ولتحقيق هذا الهدف, نستخدم بيانات سلاسل زمنية وفق تكرارات سنوية تغطي الفترة 1990-2010 (21 مشاهدة),و باستخدام أساليب الإقتصاد القياسي لإيجاد أثر الاستثمار الحكومي في قطاع الإسكان على كل من الناتج الحقيقي الإجمالي والناتج الحقيقي للقطاعات الإقتصادية الاخرى بالإضافة لأثره على التوظيف. تظهر النتائج وجود أثر إيجابي للاستثمار الحكومي في قطاع الاسكان على الناتج المحلي الحقيقي, كما تظهر وجود أثر إيجابي لهذا الاستثمار على كل من قطاع الزراعة, الصناعة والتعدين, النقل و المواصلات, التجارة الداخلية و المال و التأمين, حيث يؤدي هذا الاستثمار إلى تحفيز هذه القطاعات ما ينعكس إيجاباً على ناتجها الحقيقي, ما يؤدي الى تحقيق نموٍ اقتصاديٍ. تظهر النتائج ايضاً إن الاستثمار في قطاع الإسكان ذو أثر إيجابي على مستوى التوظيف, حيث للاستثمار في قطاع الاسكان أثار مباشرة(الاستثمار في قطاع الإسكان) و غير مباشرة(من خلال أثره على ناتج القطاعات الاخرى) تؤدي كلاها الى زيادة معدل التوظيف. This study aims to determine the economic impacts of governmental investment on housing sector in Syria. To reach this aim, we used time series data with annual recurrences in the period 1990-2010(21 observations), and by using econometrics methods to find the impact of the governmental investment on real GDP, economy’s sectors and employment. The results indicates that there is a positive impact of the governmental investment on real GDP, also a positive impact on other sectors in the economy (agriculture sector, manufacturing and mining sector, transportation sector, trade sector and banking and real estate sector). Therefore this investment leads to stimulate those sectors which will have a positive impact on economic growth. Also, the investment in housing sector has a positive impact on employment rate, because it affects, directly (through the investment) and indirectly (through affecting other sectors), therefore causing an increase in employment rate.